An unconventional family 1 uracil DNA glycosylase in Nitratifractor salsuginis. (26th October 2017) - Li, Jing; Chen, Ran; Yang, Ye; Zhang, Zhemin; Fang, Guang‐Chen; Xie, Wei; Cao, Weiguo
Abstract : The uracil DNA glycosylase superfamily consists of at least six families with a diverse specificity toward DNA base damage. Family 1 uracil N ‐glycosylase (UNG) exhibits exclusive specificity on uracil‐containing DNA. Here, we report a family 1 UNG homolog from Nitratifractor salsuginis with distinct biochemical features that differentiate it from conventional family 1 UNGs. Globally, the crystal structure of N. salsuginis UNG shows a few additional secondary structural elements. Biochemical and enzyme kinetic analysis, coupled with structural determination, molecular modeling, and molecular dynamics simulations, shows that N. salsuginis UNG contains a salt bridge network that plays an important role in DNA backbone interactions. Disruption of the amino acid residues involved in the salt bridges greatly impedes the enzymatic activity. A tyrosine residue in motif 1 (GQDPY) is one of the distinct sequence features setting family 1 UNG apart from other families. The crystal structure of Y81G mutant indicates that several subtle changes may account for its inactivity. Unlike the conventional family 1 UNG enzymes, N. salsuginis UNG is not inhibited by Ugi, a potent inhibitor specific for family 1 UNG. This study underscores the diversity of paths that a uracil DNA glycosylase may take to acquire its unique structural and biochemical properties during evolution. Database: Structure data are available in the PDB under accession numbers5X3G and5X3H . Abstract : The crystal structure and biochemical and biophysical analysis of Nitratifractor salsuginis (Nsa) family 1 uracil DNA glycosylase (UNG) demonstrate that R83 forms salt bridges with the phosphate 5′ to the deoxyuridine in DNA and D94, which in turn, is stabilized by a hydrogen bond with S86. P82 provides the rigidity in the loop to stabilize the salt bridge network.